The effect of diet fed to lambs on subsequent development of Trichostrongylus colubriformis larvae in vitro and on pasture - Niezen, J.H.; Waghorn, G.C.; Graham, T.; Carter, J.L.; Leathwick, D.M (Elsevier, 2002)
Contrasting herbage diets were fed to lambs to evaluate their effect on subsequent development of Trichostrongylus colubriformis larvae in faeces and on pasture. The diets had either no condensed tannin (CT), lucerne (Medicago sativa cv. Otaio), white clover (Trifolium repens cv. Tahora), or had moderate to high concentrations of CT, sulla (Hedysarum coronarium cv. Grassland Aokau), Lotus corniculatus (cv. Grasslands Goldie), L. pedunculatus (cv. Grassland Maku), Dorycnium pentophyllum, and Dorycnium rectum. Trials were carried out in summer (warm) and in autumn (cool and moist). In summer, egg viability was evaluated in vitro with egg hatch and larval development assays. In both seasons faeces were placed on pasture to compare recovery of eggs and larvae from faeces and larvae from herbage on the high and low fertility farmlets on the AgResearch Ballantrae Hill Country Research Station. D. rectum and D. pentophyllum diets decreased (P<0.01) egg hatching and larval development in laboratory assays relative to other diets. In summer, the number of larvae recovered from faeces placed on pasture was far greater (P<0.001) if the lambs had been fed lucerne than any other diet, whereas recovery was always lowest from faeces of sheep fed D. rectum and D. pentophyllum. Although dietary differences were lower in autumn than in summer, larval recoveries were lower (P<0.05) from faeces of lambs fed D. rectum and L. corniculatus than from white clover, lucerne and sulla diets. This study indicates that the diet of the host can have a significant impact on egg hatching and the subsequent development of T. colubriformis larvae in the laboratory and in the field. In particular, D. rectum consistently reduced T. colubriformis development. Effects measured in vitro generally under-estimated effects measured under field conditions.